STRATEGI KELUARGA MENENGAH KE BAWAH MENGHADAPI KRISIS EKONOMI PASCA PANDEMI DI LINGKUNGAN PERKOTAAN: STUDI KASUS DI DESA MERJOSARI KOTA MALANG - Aqilla Pradanimas; Ari Kamayanti (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The Covid-19 pandemic has had a serious impact on the economy of society, both in rural and urban areas. Many of them have lost their jobs and experienced deep suffering due to the pandemic, especially those in the middle and lower economic groups. This research aims to explain the strategies of lower middle class families in facing the economic crisis after the Covid-19 pandemic in urban environments. The research was conducted using a qualitative approach with a case study type. Data was collected through interview techniques with five six lower middle class families to ask about their strategies in dealing with the crisis. This research found that there are several strategies used by middle and lower class families to face their economic crisis after the Covid-19 pandemic, namely by managing the family budget wisely, creatively increasing sources of income, utilizing social assistance, improving skills to increase independent business opportunities and collaborate with the community